Financial Development, Property Rights, and Growth - Claessens, Stijn; Laeven, Luc (World Bank, Washington, DC, 2014)
The authors analyze how property rights affect the allocation of firms' available resources among different types of assets. In particular, they investigate empirically for a large number of countries whether firms in environments with more secure property rights allocate available resources more toward intangible assets and consequentially grow faster. The authors find that improved asset allocation due to better property rights has an effect on growth in sectoral value added equal to improved access to financing arising from greater financial development. The results are robust, using various samples and specifications, including controlling for growth opportunities.